The source sizes of type II radio bursts with LOFAR - Kumari, A.; Morosan, D. E.; Mugundhan, V.; Zhang, P.; Magdalenic, J.; Zucca, P.; Kilpua, E. K. J.; Daei, F. (EDP SCIENCES S A, 2026)
Context. Solar radio bursts can provide important insights into the underlying physical mechanisms that drive the small and large-scale eruptions on the Sun. Since metric radio observations can give us direct observational access to the inner and middle corona, they are often used as an important tool to monitor and understand the coronal dynamics.
Aims. While the sizes of the radio sources that can be observed in the solar corona are essential for understanding the nature of density turbulence within the solar corona and its subsequent influence on the angular broadening observed in radio source measurements, the smallest radio sources associated with solar radio bursts have so far been limited by observational techniques and the radio instrument's baselines.
Methods. We selected three type II bursts that were observed with the LOFAR core and remote stations in the Solar Cycle 24. We estimated the sizes and shapes (ellipticity) of the radio sources from 20-200 MHz using a two-dimensional (2D) Gaussian approximation.
Results. Our analysis shows that the smallest radio source size for type II bursts in the solar corona that can be observed in the solar atmosphere at low frequencies is 1.5 '+/- 0.5 ' at 150 MHz. However, even though the observations were taken with remote baselines (with a maximum distance of ∼85 km), the effective baselines were much shorter (∼15 km), likely due to snapshot imaging of the Sun. Conclusions. Our results show that the radio source sizes are less affected by scattering than suggested in previous studies. Our measurements indicate smaller source sizes at frequencies below 95 MHz compared to previous reports, though some overlap exists with measurements at higher frequencies when using smaller baselines.